One dark night - McMurray, Kevin F. (New York : St. Martin's Paperbacks, 2010)
Their neighbors were Bill and Hillary Clinton. Their home was Chappaqua, the upscale New York suburb famous for its tranquillity--until one dark night, when a brutal murder shattered the community.
Keywords: Murder -- Investigation -- New York (State); Murder -- New York (State) -- Chappaqua -- Case studies